2015
DOI: 10.5455/javar.2015.b90
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Duck Plague virus isolated from Bangladesh

Abstract: Duck plague (DP) is the most feared duck disease in the world. For isolation, identification, molecular detection and characterization of DP virus (DPV), a total of 94 samples were collected from commercial farms (n=6) and households (n=13) from Rajshahi (n=37), Netrokona (n=35) and Mymensingh (n=22) districts of Bangladesh. The samples were processed and inoculated into 11-13 days old embryonated duck eggs for virus propagation. Virus was identified using agar gel immunodiffusion test (AGIT) and passive hemag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 25 publications
7
21
2
Order By: Relevance
“…Reddish skin lesions with widespread petechiae, patches of congestion and hemorrhage on CAM of infected embryos correlate the disease with other previous studies [22]. Petechial hemorrhage and enlargement of the liver and necrotic foci on spleen [2,6] also indicate the outbreaks as DP. Our study focused down the histopathological changes of DEV-infected CAM first time which was enormous hemorrhage on CAM wall, round inflammatory zones with infiltration of mononuclear cells and heterophils.…”
Section: Discussionsupporting
confidence: 84%
“…Reddish skin lesions with widespread petechiae, patches of congestion and hemorrhage on CAM of infected embryos correlate the disease with other previous studies [22]. Petechial hemorrhage and enlargement of the liver and necrotic foci on spleen [2,6] also indicate the outbreaks as DP. Our study focused down the histopathological changes of DEV-infected CAM first time which was enormous hemorrhage on CAM wall, round inflammatory zones with infiltration of mononuclear cells and heterophils.…”
Section: Discussionsupporting
confidence: 84%
“…Duck plague considers an economic disease in Bangladesh causes higher mortality in the duck population (Hoque et al, 2010). Several studies have so far been conducted on duck plague elsewhere in Bangladesh (Hoque et al, 2011;Ahamed et al, 2015;Khan et al, 2018). The vaccine is available for duck plague but people did not use it regularly which leads to disease occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Diseases such as Newcastle disease (ND), infectious bursal disease (IBD), colibacillosis, aspergillosis, avian influenza (AI), coccidiosis, infectious bronchitis, fowl cholera, salmonellosis, mycoplasmosis, chronic respiratory diseases, necrotic enteritis in broiler and layer (Choudhary et al, 2012;Islam et al, 2014Islam et al, , 2016Badruzzaman et al, 2015;Hassan et al, 2016;Matin et al, 2017;, duck viral hepatitis, duck plague in duck (Hossain et al, 2005;Hoque et al, 2006Hoque et al, , 2010Ahamed et al, 2015;Khan et al, 2018) and pigeon fox (Paul et al, 2015;Munmun et al, 2016;Elina et al, 2017) have been reported in Bangladesh. These poultry diseases have also been recorded in other countries like India, Nigeria, China and Pakistan (Balami et al, 2014;Abbas et al, 2015;Borah et al, 2017;Ghosh et al, 2017;Xi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of DVE can also be confirmed by demonstration of the virus in tissues through FATs (Tantaswasdi et al 1988). Molecular studies and sequencing indicated close ancestry between Bangladeshi and Chinese isolates of DPV (Ahamed et al 2015).…”
Section: Diagnosismentioning
confidence: 97%
“…Subsequently, between 1970 and 1995, more than 100 outbreaks have been reported from places such as Maryland, New York, California and Pennsylvania (Hwang et al 1975;Brand & Docherty 1984;Davison et al 1993;Converse & Kidd 2001;Sandhu & Shawky 2003). In addition to outbreaks in the Netherlands and USA, DVE has been reported in China (Jansen & Kunst 1964;Wu et al 2012a), France (Gaudry et al 1970;Gough et al 1987), Belgium (Devos et al 1964), India (Mukerji et al 1963a;Duraiswami et al 1979;Rajan et al 1980), Egypt (ElSamadony et al 2013) England (Hall & Simmons 1972;Gough & Alexander 1990), Canada (Hanson & Willis 1976), Germany (Kaleta et al 2007), Denmark (Prip et al 1983), Poland (Wozniakowski & Samorek-Salamonowicz 2014), Vietnam (Pritchard et al 1999) and Bangladesh (Hoque et al 2011;OIE 2012;Ahamed et al 2015). An epidemiological study conducted in Chatkhil town of the Noakhali District of Bangladesh during January 2005-June 2006 highlighted that mortality in household ducks occurred mostly due to diseases like DP and duck cholera, and unvaccinated birds remained at higher risk.…”
Section: Epidemiology and Disease Distributionmentioning
confidence: 99%